The effect of vermicompost and NPK fertilizer on the growth of Spinach (Amaranthus tricolor) - Ahmad Raksun; I Wayan Merta; I Gde Mertha; Mohammad Liwa Ilhamdi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
Spinach is a plant usually cultivated for its leaves to be consumed as green vegetables. Spinach contains vitamins, protein, fat, carbohydrates, and minerals. Research on the effect of Vermicompost and NPK fertilizer on the growth of spinach has been carried out from July to September 2021 in Lombok, Indonesia. The objectives of the study are to determine: (1) the effect of Vermicompost on the growth of spinach, (2) the effect of NPK fertilizer on the growth of spinach, (3) the interaction effect of Vermicompost and NPK fertilizer on the growth of spinach. This research was conducted experimentally using a factorial, completely randomized design with two factors and three replications. The first factor was the dose of NPK fertilizer which consisted of 4 treatment levels, namely 0 g, 0.5 g, 1 g, and 1.5 g for each plant. The second factor is the dose of Vermicompost, which consists of 5 levels, namely 0 kg, 0.6 kg, 1.2 kg, 1.8 kg, and 2.4 kg for 1 m2 of agricultural land. The vermicompost treatment was carried out ten days before planting. The NPK fertilizer treatment was carried out ten and 20 days after planting. Spinach growth parameters were stem diameter, plant height, total leaf, leaf length, and leaf width. The results of the study were: (1) the treatment of NPK fertilizer had a significant effect on the number of leaves, leaf length, leaf width, stem height, and stem diameter of spinach, (2) the application of Vermicompost had a significant effect on the number of leaves, leaf length, leaf width, and stem height but did not significantly affect the diameter of the stems, (3) the optimum dose of NPK fertilizer was 1 gram per plant, (4) treatment 1.8 kg vermicompost resulted in better growth of spinach compared to other.